Applications of Fibonacci Numbers 1998
DOI: 10.1007/978-94-011-5020-0_34
|View full text |Cite
|
Sign up to set email alerts
|

Diophantine Properties of Linear Recursive Sequences I

Abstract: Abstract. Let Gn be a linear recursive sequence of integers and P (y) be a polynomial with integer coefficients. In this paper we are given a survey on results on the solutions of diophantine equation Gn = P (y). We prove especially that if Gn is of order three such that its characteristic polynomial is irreducible and has a dominating root then there are only finitely many perfect powers in Gn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…• If n > 2 and F n = y p then p < 5.1 × 10 17 ; this was proved by Pethő using a linear form in three logarithms [27]. In the same paper he also showed that if n > 2 and L n = y p then p < 13222 using a linear form in two logarithms.…”
Section: A Brief Survey Of Previous Resultsmentioning
confidence: 89%
“…• If n > 2 and F n = y p then p < 5.1 × 10 17 ; this was proved by Pethő using a linear form in three logarithms [27]. In the same paper he also showed that if n > 2 and L n = y p then p < 13222 using a linear form in two logarithms.…”
Section: A Brief Survey Of Previous Resultsmentioning
confidence: 89%
“…Very recently, Pethő [17] used the above result of Corvaja and Zannier to show that there are only finitely many perfect powers in a third order linear recurring sequence (G n ), if we assume that the characteristic polynomial of (G n ) is irreducible and has a dominating root.…”
Section: 1)mentioning
confidence: 99%
“…To be precise, if we apply a theorem of Mignotte [16], after reducing the problem to consideration of suitable Thue equations (see Section 2 of this paper), we obtain an upper bound for n in (1.1) of order log D. Similarly, a general result for powers in recurrence sequences due to Pethő [20] yields a bound for n in terms of the fundamental unit in Q( √ D). What is (debatably!)…”
Section: For Integers X and Q Larger Than One Then The Maximum Of Xmentioning
confidence: 81%